DESCRIPTION OF FRIENDSHIP QUALITY IN YOGYAKARTA STUDENTS - Abdillah, Muhamad Hasan; Anindita, Wiwid Dyah; Permatasari, Sita; Nabillah, Bella Rifqi; Mujidin, Mujidin (Esa Unggul University, 2020)
Friendship is an adaptive function of individual maturity to fulfill a number of social, cognitive, and emotional needs. The purpose of this study is to find out the meaning of the quality of student friendship based on the stage of development and gender. The subjects of this study were S1 and S2 students in Yogyakarta with 200 students. The sampling technique used was a non-probability convenience sampling technique. The data collection tool is a closed and open questionnaire, with content analysis as the analysis of the data. The results showed that in the late male adolescent group, individuals felt close to their best friend, in the late adolescent group of women, individuals felt they believed their best friend could be a confidant who was able to provide solutions, in the early adult groups of men understanding and supporting each other as reasons the quality of friendship is broken, and in the early adult groups women confide in and believe as the reason for the quality of friendship. The conclusion is the reason for the quality of friendship based on the stages of development and gender there are differences, but in adolescent and adult women there are similarities.